The impact of low-luminosity AGNs on their host galaxies: a radio and optical investigation of the kiloparsec-scale outflow in MaNGA 1-166919 - Yazeedi, Aisha Al; Katkov, Ivan Yu; Gelfand, Joseph D.; Wylezalek, Dominika; Zakamska, Nadia L.; Liu, Weizhe (The astrophysical journal, 2021)
One way an active galactic nucleus (AGN) influences the evolution of their host galaxy is by generating a large-scale (kiloparsec-scale) outflow. The content, energetics, and impact of such outflows depend on the properties of both the AGN and host galaxy, and understanding the relationship between them requires measuring the properties of all three. In this paper, we do so by analyzing recent radio and optical integral field unit spectroscopic observations of MaNGA 1-166919. Our results indicate that the biconical outflow in this galaxy is powered by a low-luminosity, low Eddington ratio AGN ejecting material that drives ∼100-200 km s−1 shocks into the surrounding interstellar medium—producing the hot, ionized gas and relativistic particles associated with the observed outflow. The energetics of the relativistic and ionized gas material produced at this shock are comparable, and both the mass outflow and kinetic power of the ionized gas in this outflow are higher than other AGNs with similar bolometric luminosities. Lastly, while the host galaxy’s total star formation rate is comparable to that of other star-forming galaxies with a similar stellar mass, there is evidence that the outflow both suppresses and enhances star formation in its immediate surroundings.
Gesehen am 11.10.2021